Mekanisme Penilaian Kinerja Karyawan pada Dinas Perhubungan Kabupaten Malang - Ria Ria; R.M Mahrus Ali (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study analyzes the employee performance assessment system at the Malang Regency Transportation Office, based on observations and interviews with several employees. Performance assessments are carried out annually with quarterly evaluations by the head of the sub-division. Evaluations include employee performance, financial administration, and staffing. The assessment process involves several stages: Annual Work Plan (RKT), Performance Agreement, Employee Performance Targets (SKP), and the use of the